Mathematical modeling learning design using Model-Eliciting Activities (MEAs) approach to two variable linear equation system material. (February 2020) - Pitriana, N; Darmawijoyo; Susanti, E
Abstract: This study aims to produce a trajectory of mathematics modeling learning with the context of Malnutrition in Indonesia using Model-Eliciting Activities (MEAs) approach in the of two-variable linear equation system material. In mathematics modeling classes, students learn to solve real problems using mathematical procedures and concepts. The method used is a study validation type research design that aims to prove learning theories. This research design consists of three stages; preliminary design, teaching experimentation, and retrospective analysis. The subjects of the study are Grade VII students of Public JHS 21 Palembang. Data collection techniques used are video recording, interviews, and documentation. Data were analyzed by comparing Hypothetical Learning Trajectory (HLT) and what happened during the learning process. This research produces a learning path of mathematical modeling using Model-Eliciting Activities (MEAs) approach with the context of Malnutrition in Indonesia in the two-variable linear equation system material. The results of this study indicate that through a series of mathematical modeling activities using Model-Eliciting Activities (MEAs) approach can help students in understanding two-variable linear equation system material.